2019
DOI: 10.1038/s41436-019-0559-1
|View full text |Cite
|
Sign up to set email alerts
|

ADDENDUM: Genetic counseling and testing for Alzheimer disease: joint practice guidelines of the American College of Medical Genetics and the National Society of Genetic Counselors

Abstract: with the following addendum: We suggest the following considerations in reaffirming this document: 1. To use the phrase "pathogenic variant" rather than the word "mutation" in discussing pathogenic variants related to autosomal dominant early-onset Alzheimer disease. This would be consistent with current ACMG/AMP Guidelines for Variant Interpretation and Reporting 1. 2. Because this document no longer meets the criteria for an evidence-based practice guideline by either the American College of Medical Genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…691, 2017; Committee Opinion No. 693, 2017; Goldman et al, 2019; Hampel et al, 2015; Ormond et al, 2021; Robson et al, 2015). Previous research demonstrated that pre‐test counseling lowered patient anxiety (Bowen et al, 2006; Pieterse et al, 2011; Roshanai et al, 2009) and increased patient understanding of the benefits and risks of genetic testing (Bowen et al, 2006; Brain et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…691, 2017; Committee Opinion No. 693, 2017; Goldman et al, 2019; Hampel et al, 2015; Ormond et al, 2021; Robson et al, 2015). Previous research demonstrated that pre‐test counseling lowered patient anxiety (Bowen et al, 2006; Pieterse et al, 2011; Roshanai et al, 2009) and increased patient understanding of the benefits and risks of genetic testing (Bowen et al, 2006; Brain et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…691, 2017;Committee Opinion No. 693, 2017;Goldman et al, 2019;Hampel et al, 2015;Ormond et al, 2021;Robson et al, 2015).…”
Section: Introductionunclassified